2020
DOI: 10.1183/16000617.0154-2020
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life of patients with idiopathic pulmonary fibrosis: a systematic review and meta-analysis

Abstract: Idiopathic pulmonary fibrosis (IPF) is one of the most common forms of interstitial lung disease presenting in persons 50 years and older. Through a comprehensive review of available studies, we aimed to assess health-related quality of life (HRQoL) of people living with IPF and the instruments used in this assessment.Searches were conducted up to May, 2020. Quality appraisal and data extraction were performed using pre-designed forms. Narrative synthesis approach was used to report results of the systematic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 174 publications
(56 reference statements)
4
40
0
Order By: Relevance
“… 30 Many different instruments have been used to assess HRQL in patients with IPF, one of the most used is the SF-36, 3 31 which have been demonstrated as a valid questionnaire. 32 Patients with IPF have significantly impaired HRQL in both Physical and Mental Summary Scores, 3 32 however, recently Cox et al 31 showed that domain scores reflecting physical wellness (activity and symptoms) were generally worse than those reflecting emotional wellness (impact), which agrees with the findings of this study. No factor was associated with the Mental Summary Score of the SF-36.…”
Section: Discussionsupporting
confidence: 89%
“… 30 Many different instruments have been used to assess HRQL in patients with IPF, one of the most used is the SF-36, 3 31 which have been demonstrated as a valid questionnaire. 32 Patients with IPF have significantly impaired HRQL in both Physical and Mental Summary Scores, 3 32 however, recently Cox et al 31 showed that domain scores reflecting physical wellness (activity and symptoms) were generally worse than those reflecting emotional wellness (impact), which agrees with the findings of this study. No factor was associated with the Mental Summary Score of the SF-36.…”
Section: Discussionsupporting
confidence: 89%
“…The low SF-36 scores in this cohort were actually lower in all subscale scores than those reported for breast cancer survivors with lymphoedema where HRQoL would be expected to be much lower [ 62 ]. Previously reported SF-36 results for patients with cirrhosis and idiopathic pulmonary fibrosis have shown PCS scores comparable to our study’s cohort, while the MCS scores in our cohort were lower than those reports [ 63 , 64 ]. Additionally, even after a significant increase in these scores at 12 months, this cohort still had scores that were much lower than the Australian adult population norms [ 49 ].…”
Section: Discussionsupporting
confidence: 59%
“…Irrespective of the ILD phenotype, disease progression is commonly associated with high symptom burden, reduced quality of life and higher HRU, and negatively impacts mental health 60–63 . A systematic review and meta‐analysis of 134 studies aimed to assess health‐related quality of life (HRQoL) of people living with IPF and patient‐reported outcome measures used in IPF studies 64 . Analysis of standardized means for both St George's Respiratory Questionnaire and Short Form 36 demonstrated worse score in physical health domains compared to mental health domains.…”
Section: What Matters To Patientsmentioning
confidence: 99%